Sustainability – Driven Entrepreneurship: The Mediating Effect of Opportunity-Based Management Structure on the Relationship between Entrepreneurial Orientation and Environmental Sustainability Management of SMEs: A Conceptual Framework - Abdul Majid , Izaidin; Kamaludin, Muhammad Hasfarizal; Md.Saad, Mohd Shamsuri; Ab. Aziz, Norazlina (2012)

(untitled)
Generally, Small and Medium-sized Enterprises have been given high priority in Malaysia and identified as one of the engines of economic growth to drive Malaysia towards the New Economic Model (NEM) transformation. However, the environmental sustainability management of SMEs need to be taken into deep consideration in order to ensure sustainable entrepreneurship in Malaysia. This study focuses on the relationship between entrepreneurial orientation and opportunity–based management structure on environmental sustainability management of small to medium-sized enterprises (SMEs) with the prime intention to enlarge the element of sustainable entrepreneurship. The problem to be addressed in this quantitative study is to look into the level of commitment of entrepreneurial firm in indicate towards the effort to ensure sustainability of environment; the main concern of entrepreneurial firm in making as much profit and growth, it is also the importance of the society to know their perceptions and commitment towards maintaining the environment. Therefore, the main focus will be given on the relationship between Entrepreneurial Orientation (EO) and Opportunity-based Management Structure with environmental sustainability management in the Malaysian SMEs context. Finally, this paper concludes by presenting the conceptual framework of entrepreneurial orientation, opportunity-based management structure and environmental sustainability management in SMEs. Keywords: Effect, Relationship, Malaysian small and medium-sized enterprises, Opportunity-based management structure, Entrepreneurial orientation, Environmental sustainability managemen